Rubber Tapper and Narrative Representation - Pizarro-Romero, A (PONTIFICIA UNIV JAVARIANA, FAC ESTUDIOS AMBIENTALES & RURALES, 2015)
Sometimes narratives can give a reductionist perception of workers. It is the case of the novel of Mario Vargas Llosa El sueno del celta ( 2011). In his discourse, the Peruvian writer explains historic events of rubber workers in which Irish Roger Casement participated. Vargas Llosa refers to a published research about the problems faced by the workers. However, he fails to notice that these workers are the same in Congo and in Amazonia: they only work, they have no other dimension and never become true human beings. Therefore, there is in this reductionist narrative an occidentalist discourse.